Musical Manifestations of Textual Patterning in Estonian Regilaul - Janika Oras (Journal of Ethnology and Folkloristics)
The article analyses the marking of song text patterns by means of musical devices in the performances of Estonian regilaul. The article examines which variants of musical rhythm and melodic contour are preferred by four singers in their performance of verses that have different functions within the song structure. In both the text and the musical rhythm, a greater number of syllables, and the attendant changes in musical rhythm, mark the verses that have an initiating function and which communicate entirely new information. In performing such verses, rather than the extension verses of parallelism groups or verse repetitions, in the short melodies with narrow pitch range, the singers prefer more "intense" variants of melody contours in which the higher notes of the scale are predominantly used. In two-line melodies, the singer's patterning of the song text is largely determined by the musical logic, attempting to align the beginnings of the melodic strophes and verse groups.